Implementasi Flipbook Materi Sistem Pertahanan Tubuh untuk Mendukung SDGs pada Hasil Belajar Siswa SMAN 2 Tenggarong - Destyara, Edita; Nasution, Ruqoyyah; Jailani, Jailani; Serena, Nelda Anasthasia; Rambitan, Vandalita Maria Magdalena (Biocaster : Jurnal Kajian Biologi, 2025)
The low level of students' understanding of Biology material, especially on the topic of the body's defense system, is often caused by limitations in the variety of learning media used. This study aims to analyze the effect of the use of flipbook-based learning media on student learning outcomes on body defense system materials, in order to support the implementation of the Sustainable Development Goals (SDGs) at SMA Negeri 2 Tenggarong. This study uses a quasi-experimental approach with purposive sampling techniques, involving 35 students divided into experimental and control groups. The research instrument consists of learning outcome tests and questionnaires, which are used to measure students' cognitive achievement. Data analysis was carried out through hypothesis tests using independent sample t-test and N-gain calculation. The results showed a significant difference between the experimental and control groups, with a significance value of the t-test of 0.00 (< 0.05), and an N-gain value of 0.73 which was categorized as a fairly effective improvement. Flipbook media has been proven to have a positive influence on student learning outcomes in the experimental group. The increase was influenced by internal and external factors, including the quality of flipbook content, the support of learning facilities, and students' motivation and interest in learning. Thus, flipbook learning media can be considered an effective alternative in increasing students' understanding of the body defense system material, as well as contributing to improving the quality of education in line with the Sustainable Development Goals (SDGs).